Analyzing the Relationship between Foreign Direct Investment and Privatization in the European Union Founder Nations by Using Panel Data Approach - Tüzüntürk, Selim; İnam, Betül and Giray, Filiz (Panoeconomicus, 2018)
Foreign direct investment (FDI) and privatization are two of the most important component in liberalization World. The aim of this study is to analyze whether there exist a statistically significant relationship between FDI and privatization, or not. To do so, a panel data sample of fourteen European Union (EU) Founder Nations in 1998-2012 was used to estimate various Panel Data Models. The special feature of panel data is that it allows researchers to construct and test more realistic behavioral models that could not be identified using cross section or time series data alone. Based on the sample results, between privatization as the primary independent variable and FDI was found to have a statistically significant positive relationship. Although other explanatory variables such as growth, trade openness, and corruption perceptions index, were found to have statistically significant effects on FDI, budget deficit was found to be statistically insignificant. Moreover, statistically significant parameters’ signs showed that all of the economic expectations were satisfied. Key words: Privatization, Foreign direct investment, European Union, Panel data. JEL: L33, G28, O52, P45, F21. Analiza odnosa između stranih direktnih investicija i privatizacije u zemljama osnivačima Evropske unije korišćenjem pristupa panel podataka Strane direktne investicije (FDI) i privatizacija su dve najvažnije komponente u svetu liberalizacije. Cilj ovog rada je da analizira da li postoji statistički značajan odnos između FDI i privatizacije ili ne. U tu svrhu korišćen je uzorak panel podataka od četrnaest zemalja članica osnivača Evropske unije (EU) u 1998-2012. godini za procenu različitih modela. Posebna karakteristika panel podataka je da omogućava istraživačima da konstruišu i testiraju realističnije modele ponašanja koji se ne mogu identifikovati koristeći samo podatke o preseku ili vremenskoj seriji. Na osnovu rezultata uzorka, između privatizacije kao primarne nezavisne varijable i FDI-a je utvrđeno da postoji statistički značajan pozitivan odnos. Iako druge uticajne varijable kao što su rast, otvorenost trgovine i indeks percepcije korupcije, takođe imaju statistički značajne efekte na FDI, utvrđeno je da budžetski deficit nije statistički značajan. Štaviše, znaci statistički značajnih parametara pokazali su da su sva ekonomska očekivanja ispunjena. Ključne reči: Privatizacija, strane direktne investicije, Evropska unija, panel podaci.